Blockchain‐based indoor location paging and answering service with truncated‐geo‐indistinguishability. Issue 2 (16th October 2021) - Yang, Changxin; Ju, Xuan; Liu, Erwu; Geng, Yuanzhe; Wang, Rui
Abstract: Indoor location‐based services have numerous applications built on indoor navigation. Over the years, researchers have proposed various indoor navigation methods to find a certain point of interest. This paper proposes location paging and answering service (LPAS) for finding out someone in an indoor environment . However, it may face serious problems of privacy disclosure of the clients' indoor location data . To ensure security, privacy and convenience, the authors leverage blockchain to model the indoor environment, and build blockchain‐based indoor LPAS (BILPAS) on blockchain by embedding our three‐way‐handshake Diffie–Hellman Key Agreement procedures. Our BILPAS can automatically establish a secure and privacy communication tunnel between any two users, thus greatly liberating participants from unnecessary self‐determining interactions . On the premise that the certain person can also be found, the authors introduce Truncated‐Geo‐Indistinguishability (TGeoI) to perturb the actual location within a limited, valid, user‐defined distance, thereby allowing users to obtain reasonable location privacy. The authors have put a strong emphasis in the formal treatment of the reasonable privacy guarantees, giving a rigorous definition of TGeoI and providing a comparison with Geo‐Indistinguishability that the authors' method satisfies such property. Then, the authors present the BILPAS prototype and implement it on Hyperledger Fabric. Finally, the authors conduct the security and privacy analysis and evaluate the time performance. The experiment results validate the reasonable privacy, high security and convenience of the authors' framework.